An Improved Genetic Algorithm For Power Losses Minimization Using Distribution Network Reconfiguration Based On Re-Rank Approach - Shamsudin, Nur Hazahsha; Omar, Nurul Farhana; Abdullah, Abdul Rahim; Sulaima, Mohamad Fani; Abidullah, Noor Athira; Jaafar, Hazriq Izzuan (Maxwell Scientific Publications, 2014)
-